2012
DOI: 10.5923/j.eee.20110101.01
|View full text |Cite
|
Sign up to set email alerts
|

The Design of a 0.35THz Microstrip Patch Antenna on LTCC Substrate

Abstract: A microstrip patch antenna on Low Temperature Co-fired Ceramic (LTCC) substrate operating at 350GHzfor THz communication has been designed. CST MWS package has been used for simulation and S 11 reached a minimum of -25.6dB at 349GHz with 8.6% bandwidth. The maximum gain achieved is 5dBi. Furthermore, a prototype for a downscaled antenna designed at 10GHz with available FR4 substrate has been fabricated and measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The theoretical resonant frequency of the SRR/TW unit cell is 10 GHz, according to the theories developed in Ref. , which is matched with the operating frequency of the patch antenna. The transversal periodicity is a = 3.5 mm, which is less than 1/8 of the free space wavelength at resonance, which is used to construct the 2D MTM periodic structure to employ the MTM lens as will be illustrated in the next section.…”
Section: Analysis and Design Of Proposed Antennamentioning
confidence: 93%
See 2 more Smart Citations
“…The theoretical resonant frequency of the SRR/TW unit cell is 10 GHz, according to the theories developed in Ref. , which is matched with the operating frequency of the patch antenna. The transversal periodicity is a = 3.5 mm, which is less than 1/8 of the free space wavelength at resonance, which is used to construct the 2D MTM periodic structure to employ the MTM lens as will be illustrated in the next section.…”
Section: Analysis and Design Of Proposed Antennamentioning
confidence: 93%
“…Here, a unit cell of SRR/TW with negative effective permittivity ( ε r ) and negative effective permeability (μ r ) is designed. The dimensions of the SRR/TW unit cell are designed and optimized in order to give a simultaneous negative permittivity and negative permeability in a frequency range to be matched with the bandwidth of the patch antenna designed in the last subsection , to achieve an optimal beam focusing when it is integrated with the patch antenna. The SRR is a copper layer with thickness t of 35 μm mounted on the top side of a RT/Duriod 5880 dielectric substrate with relative dielectric permittivity ε r of 2.2 and height h = 1.57 mm, and the TW is mounted on the other side, i.e.…”
Section: Analysis and Design Of Proposed Antennamentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the electromagnetic waves in the media can be congregated in a narrow rectangle area properly when applied to a monopole antenna; this structure can greatly improve the directivity of the antenna. Also, metamaterials have been designed and investigated in the THz frequency range for developing new THz devices such as antennas, filters, sensors, and absorbers [31][32][33][34]. Furthermore, metamaterial structures composed of 3-D metal grid superstrate have been used to improve the directivity of the antenna [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The terahertz spectrum has many unique radiation characteristics as high image resolution, high level of wave penetration and low ionization in biological tissues [2]. Microstrip antenna has been introduced to terahertz communication because of its simplicity of fabrication and compactness [3,4]. The microstrip antenna has small-size, low-cost, reliability configurability and suitability for diversity.…”
Section: Introductionmentioning
confidence: 99%